Correlation of Obesity and Osteoporosis: Effect of Fat Mass on the Determination of Osteoporosis - Zhao, Lan‐Juan; Jiang, Hui; Papasian, Christopher J; Maulik, Dev; Drees, Betty; Hamilton, James; Deng, Hong‐Wen (Journal of bone and mineral research, 2008)
It was previously believed that obesity and osteoporosis were two unrelated diseases, but recent studies have shown that both diseases share several common genetic and environmental factors. Body fat mass, a component of body weight, is one of the most important indices of obesity, and a substantial body of evidence indicates that fat mass may have beneficial effects on bone. Contrasting studies, however, suggest that excessive fat mass may not protect against osteoporosis or osteoporotic fracture. Differences in experimental design, sample structure, and even the selection of covariates may account for some of these inconsistent or contradictory results. Despite the lack of a clear consensus regarding the impact of effects of fat on bone, a number of mechanistic explanations have been proposed to support the observed epidemiologic and physiologic associations between fat and bone. The common precursor stem cell that leads to the differentiation of both adipocytes and osteoblasts, as well the secretion of adipocyte‐derived hormones that affect bone development, may partially explain these associations. Based on our current state of knowledge, it is unclear whether fat has beneficial effects on bone. We anticipate that this will be an active and fruitful focus of research in the coming years.